Effect of sodium doping on crystal growth and band matching of the heterojunction in flexible CZTS solar cells. Issue 48 (1st December 2021) - Zhao, Qichen; Shen, Honglie; Gao, Kai; Xu, Yajun; Wang, Xuewen; Li, Yufang
Abstract : Flexible Cu2 ZnSnS4 solar cells were doped with sodium using a novel method, which effectively facilitated carrier collection in a heterojunction and demonstrated favorable bending stability. Abstract : Treating kesterite layers with sodium has been proved to be an effective way to improve the photovoltaic performance of Cu2 ZnSnS4 (CZTS) solar cells. However, elemental diffusion effects inside the film and heterojunction energy band matching on the performance of flexible solar cells are rarely reported. In this work, flexible CZTS solar cells were doped with various sodium sources using a simple solution spin-coating post-treatment method. The research results demonstrated that films prepared by Na2 S2 O3 solution doping exhibit improved crystalline quality and photoelectric properties, while also inhibiting the growth of impurity defects within the films. Further optimization of the doping concentration of post-treatment solution showed that when the doping ratio was 0.05 mmol mL −1, the grain growth of the prepared film was larger, and adhesion between the film layers was enhanced. The energy band bending of the CZTS/CdS heterojunction exhibited a "cliff" arrangement when the conduction band offset (CBO) value was −0.34 eV, facilitating carrier transport in the space charge region and enhancing the collection of photogenerated carriers. The flexible CZTS solar cell constructed on this basis exhibited excellent bending resistance and a maximum photoelectric conversion efficiency (PCE) of 5.83% with an open-circuit voltage ( V oc ) of 609 mV.